LC3B globular structures correlate with survival in esophageal adenocarcinoma - O'SULLIVAN, JACINTHA; REYNOLDS, JOHN (My University, 2015)
Background Esophageal adenocarcinoma has the fastest growing incidence of any solid tumor in the Western world. Prognosis remains poor with overall five-year survival rates under 25 %. Only a limited number of patients benefit from chemotherapy and there are no biomarkers that can predict outcome. Previous studies have indicated that induction of autophagy can influence various aspects of tumor cell biology, including chemosensitivity. The objective of this study was to assess whether expression of the autophagy marker (LC3B) correlated with patient outcome. Methods Esophageal adenocarcinoma tumor tissue from two independent sites, was examined retrospectively. Tumors from 104 neoadjuvant naïve patients and 48 patients post neoadjuvant therapy were assembled into tissue microarrays prior to immunohistochemical analysis. Kaplan-Meier survival curves and log-rank tests were used to assess impact of LC3B expression on survival. Cox regression was used to examine association with clinical risk factors. Results A distinct globular pattern of LC3B expression was found to be predictive of outcome in both patient groups, irrespective of treatment (p < 0.001). Multivariate analysis found that this was a strong independent predictor of poor prognosis (p < 0.001). Conclusions This distinctive staining pattern of LC3B represents a novel prognostic marker for resectable esophageal adenocarcinoma.
PUBLISHED
Keywords: Esophageal adenocarcinoma; Esophageal adenocarcinoma